N-Acetyl-Cysteine-Loaded Biomimetic Nanofibrous Scaffold for Osteogenesis of Induced-Pluripotent-Stem-Cell-Derived Mesenchymal Stem Cells and Bone Regeneration - Li, Xiaolei; Xiong, Feng; Wang, Shuguang; Zhang, Zhuojun; Dai, Jihang; Chen, Hui; Wang, Jingcheng; Wang, Qiang; Yuan, Huihua (Frontiers in Bioengineering and Biotechnology, 2021)
To regenerate bone tissues, we investigated the osteogenic differentiation of induced-pluripotent-stem-cell-derived mesenchymal stem cells (iPSC-MSCs) and bone regeneration capacities using N-acetyl cysteine (NAC)-loaded biomimetic nanofibers of hydroxyapatite/silk fibroin (HAp/SF). The addition of HAp and NAC decreased the diameters of the electrospun fibers and enhanced the mechanical properties of the silk scaffold. The release kinetic curve indicated that NAC was released from NAC/HAp/SF nanofibers in a biphasic pattern, with an initial burst release stage and later sustained release stage. This release pattern of NAC encapsulated on the NAC/HAp/SF scaffolds prolonged the release of high concentrations of NAC, thus largely affecting the osteogenic differentiation of iPSC-MSCs and bone regeneration. Thus, a new silk electrospun scaffold was developed. HAp was used as a separate nanocarrier for recharging the NAC concentration, which demonstrates the promising potential for the use of NAC/HAp/SF for bone tissue engineering.